Tocolysis with nifedipine versus atosiban and perinatal outcome: an individual participant data meta-analysis - Tijn M. S. van Winden; Tobias A. J. Nijman; C. Emily Kleinrouweler; Raed Salim; Maryam Kashanian; Wafa R. Al-Omari; Eva Pajkrt; Ben W. Mol; Martijn A. Oudijk; Carolien Roos (BMC, 2022)
Abstract Background Worldwide, nifedipine and atosiban are the two most commonly used tocolytic agents for the treatment of threatened preterm birth. The aim of this study was to evaluate the effectiveness of nifedipine and atosiban in an individual participant data meta-analysis (IPDMA). Methods We investigated the occurrence of adverse neonatal outcomes in women with threatened preterm birth by performing an IPDMA, and sought to identify possible subgroups in which one treatment may be preferred. We searched PubMed, Embase, and Cochrane for trials comparing nifedipine and atosiban for treatment of threatened preterm birth between 240/7 and 340/7 weeks' gestational age. Primary outcome was a composite of perinatal mortality and neonatal morbidities including respiratory distress syndrome, intraventricular haemorrhage, periventricular leucomalacia, necrotising enterocolitis, and sepsis. Secondary outcomes included NICU admission, prolongation of pregnancy and GA at delivery. For studies that did not have the original databases available, metadata was used. This led to a two-stage meta-analysis that combined individual participant data with aggregate metadata. Results We detected four studies (N = 791 women), of which two provided individual participant data (N = 650 women). The composite neonatal outcome occurred in 58/364 (16%) after nifedipine versus 69/359 (19%) after atosiban (OR 0.76, 95%CI 0.47-1.23). Perinatal death occurred in 14/392 (3.6%) after nifedipine versus 7/380 (1.8%) after atosiban (OR 2.0, 95%CI 0.80-5.1). Nifedipine results in longer prolongation of pregnancy, with a 18 days to delivery compared with 10 days for atosiban (HR 0.83 (96% CI 0.69-0.99)). NICU admission occurred less often after nifedipine (46%) than after atosiban (59%), (OR 0.32, 95%CI 0.14-0.75). The sensitivity analysis revealed no difference in prolongation of pregnancy for 48 hours (OR 1.0, 95% CI 0.73-1.4) or 7 days (OR 1.3, 95% CI 0.85-5.8) between nifedipine and atosiban. There was a non-significant higher neonatal mortality in the nifedipine-exposed group (OR 1.4, 95% CI 0.60-3.4). Conclusions In this IPDMA, we found no differences in composite outcome between nifedipine and atosiban in the treatment of threatened preterm birth. However, the non-significant higher mortality after administering nifedipine warrants further investigation of the use of nifedipine as a tocolytic drug. Study registration We conducted this study according to a prospectively prepared protocol, registered with PROSPERO (the International Prospective Register of Systematic Reviews) under CRD42016024244.